2018
DOI: 10.1177/1473095218764225
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of self-organization in the context of urban planning: Reconsidering venues of participation

Abstract: This article unpacks the relations that exist between the planning institution and urban residents by examining processes of self-organization in planning. Approaching self-organization with the lens of assemblage, the article proposes three categories or patterns of self-organization of different urban actors and portrays how they act in different forms to induce urban change. The three self-organization categories are as follows: (1) self-organization by the disenfranchised for basic rights, (2) self-organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…However, community groups have uneven abilities to develop discursive and material support networks, which means that groups that would benefit from opportunities to gain social capital through community organising might be excluded (Ghose and Pettygrove, 2014b; Smith and Kurtz, 2003). This strand of research on community gardens aligns with wider debates in the literature on self-organisation and participatory democracy in which research has found that seemingly empowering mechanisms for self-advocacy amplify, rather than even out, social inequalities (Cooke and Kothari, 2001; Eizenberg, 2018; Swyngedouw, 2005; Van Holstein, 2018).…”
Section: Community Garden Network and Subjectivitysupporting
confidence: 55%
See 3 more Smart Citations
“…However, community groups have uneven abilities to develop discursive and material support networks, which means that groups that would benefit from opportunities to gain social capital through community organising might be excluded (Ghose and Pettygrove, 2014b; Smith and Kurtz, 2003). This strand of research on community gardens aligns with wider debates in the literature on self-organisation and participatory democracy in which research has found that seemingly empowering mechanisms for self-advocacy amplify, rather than even out, social inequalities (Cooke and Kothari, 2001; Eizenberg, 2018; Swyngedouw, 2005; Van Holstein, 2018).…”
Section: Community Garden Network and Subjectivitysupporting
confidence: 55%
“…Uitermark (2015) calls for research that recognises the potential of self-organisation and is critical of the uneven politics that promote it. Concurrently, Eizenberg (2018) offers insight into the multiple objectives of self-organisation and how it can advance the interests of the disenfranchised and the privileged. The work presented in this paper shows that the process of gentrification creates extra tensions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Common channels include turning to the court, submitting petitions, and conducting meetings with various municipal workers (Islam and Sakizlioglu 2015; Bhan 2009; Jabareen and Switat 2019; Zaman 1996; Newman and Wyly 2006; Chatterjee 2014; Roy 2017). The formation of residents’ associations and alternative housing organizations that fight rent escalation are also considered a form of resistance (Eizenberg 2019; Rodriguez and Di Virgilio 2016; Annunziata and Lees 2016), as are demonstrations (Goodman 1971; Newman and Wyly 2006; Smith 2002; Slater 2006; Förste and Bernt 2018; Naeglar 2012; Bob and Majola 2011; Maiello and Pasquinelli 2015; Bhan 2009; Müller 2015; Silvestre and de Oliveira 2012; Goldman 2011; Roy 2017). In most cases, resistance will be practiced through more than one channel.…”
Section: The Concepts Of the Urban Displacement Frameworkmentioning
confidence: 99%